CEO-CFO SOCIAL TIES, KOMPETENSI AUDITOR INTERNAL, DAN MANAJEMEN LABA - Khairanis Yulita (Jurnal Akuntansi Trisakti, 2021)
Social ties can be a synergy to increase or decrease a distortion. Jiwasraya phenomenon in Indonesia is one example of the social ties between Chief Executive Officer and Chief Financial Officer being abused to conspire and beautify financial reports by earnings management. Internal auditor have a role to ensure that all company operations do not deviate from existing standards and regulations. The purpose of this study is to examine the effect of Chief Exeutive Officer-Chief Financial Officer social ties on earnings management and to interact that effect with internal auditors competency, which is the difference between this study and previous research. The research samples are non-financial state-owned companies listed on the IDX for the 2015-2019 period with a total of 79 companies. The research method uses Moderated Regression Analysis. The results show that Chief Exeutive Officer-Chief Financial Officer social ties has a negative effect on earnings management and internal auditor’s competency doesnt not moderate that effect. The conclusion of this study is the social ties that exist between the board directors, especially CEO and CFO can increase synergy and cooperation in the way to minimize opportunistic behavior. Future research can consider another proxy for social ties especially personal ties and also internal audit function.